PUSAT PERMAINAN TRADISIONAL ANAK DI KOTA BANJARBARU - Rashifa, Shahnaz Alya; Mentayani, Ira (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
As time goes by, today's children begin to entertain themselves with modern games, causing traditional games to lose their existence. Therefore, Banjarbaru City made efforts to preserve traditional games by organizing traditional game competitions which were attended by several students in Banjarbaru. In addition, Banjarbaru City was also named as a Child Friendly City with the issuance of regional regulation Number 16 of 2019. To support the fulfillment of children's rights contained in the regulation and the unavailability of a place that can accommodate the introduction, preservation, and playing facilities of traditional games in Banjarbaru, there is a need for a Children's Traditional Game Center in Banjarbaru City. To solve the design problem, the concept of educational recreation is used as a form of activity, physical, and spatial embodiment that can make children feel happy, entertained, happy while getting lessons about traditional games in this game center and the concept is combined with the Architectural Psychology method as an age limit for actors and a benchmark for the physical embodiment of the design.